Review of recent advances of free-piston internal combustion engine linear generator. (1st July 2020) - Guo, Chendong; Zuo, Zhengxing; Feng, Huihua; Jia, Boru; Roskilly, Tony
Highlights: Recent technical advances of free-piston internal combustion engine linear generator are discussed. Modeling and simulation method, experimental approach, and control strategies development are reviewed respectively. Research trend and future development are prospected. Abstract: Free piston internal combustion engine linear generator (FPELG) is a novel energy conversion device. Compared with traditional rotary internal combustion engines, FPELG shows many potential advantages due to the elimination of crank-connecting rod mechanism, such as structure simply, the high thermal efficiency, the low emission, the multi-fuel and the multi combustion mode feasibility. Therefore, the FPELG has become a research hot-point in recent years and has achieved a lot of research results. This paper mainly discusses and summarizes the recent technical advances of the FPELG from the research groups worldwide. After a brief introduction on the early research of the free-piston internal combustion engines, its working principle and different configurations are introduced respectively. Then, this paper mainly focuses on the recent research progress of the FPELG from the aspects of modeling and simulation method, experimental approach, and control strategies development. In the end of the paper, the research trend and future development of the FPELG will be prospected. It is concluded that matching and optimizing performances of free-piston internal combustion engine and linear generator are the key research points, and the controlled piston trajectory of the FPELG is the key technology.